2005
DOI: 10.1080/10473289.2005.10464779
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Mechanism for Mercury Oxidation on Selective Catalytic Reduction Catalysts under Coal-Derived Flue Gas

Abstract: This paper introduces a predictive mechanism for elemental mercury (Hg 0 ) oxidation on selective catalytic reduction (SCR) catalysts in coal-fired utility gas cleaning systems, given the ammonia (NH 3 )/nitric oxide (NO) ratio and concentrations of Hg 0 and HCl at the monolith inlet, the monolith pitch and channel shape, and the SCR temperature and space velocity. A simple premise connects the established mechanism for catalytic NO reduction to the Hg 0 oxidation behavior on SCRs: that hydrochloric acid (HCl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 12 publications
7
110
1
3
Order By: Relevance
“…The steep rise in mercury oxidation at low HCl volume fractions is in contrast to the behavior predicted by Niksa and Fujiwara (2005b) in the presence of both NO and NH 3 . In a square honeycomb catalyst at 364 o C, at an NH 3 /NO ratio of 0.9 and space velocity of 3930 h -1 , those authors' calculations showed that the fraction of mercury oxidized at the exit from the catalyst increased approximately linearly from 0 at low HCl volume fractions, to only 14% of mercury oxidized in the presence of 25 ppmv HCl.…”
Section: Dependence Of Mercury Oxidation On Hclcontrasting
confidence: 69%
See 2 more Smart Citations
“…The steep rise in mercury oxidation at low HCl volume fractions is in contrast to the behavior predicted by Niksa and Fujiwara (2005b) in the presence of both NO and NH 3 . In a square honeycomb catalyst at 364 o C, at an NH 3 /NO ratio of 0.9 and space velocity of 3930 h -1 , those authors' calculations showed that the fraction of mercury oxidized at the exit from the catalyst increased approximately linearly from 0 at low HCl volume fractions, to only 14% of mercury oxidized in the presence of 25 ppmv HCl.…”
Section: Dependence Of Mercury Oxidation On Hclcontrasting
confidence: 69%
“…As previously noted in work by others, mercury oxidation in SCR catalyst was highly sensitive to the concentration of HCl at low levels of HCl (< 10 ppmv) (Eswaran and Stenger, 2005), and is suppressed in the presence of NH 3 (Machalek et al, 2003;Niksa and Fujiwara, 2005b;Senior, 2006;Gale et al, 2006b), because NH 3 competes with one of more of the reactants (Hg, HCl) for active sites on the surface of the catalyst.…”
Section: ____________________________________________________________mentioning
confidence: 69%
See 1 more Smart Citation
“…However, when supported vanadia systems were studied by Vittadini et al, 20 the unit cell used was small, causing vanadia dimers to cover almost the entire surface, which is not a reasonable representation of the low loading associated with SCR systems. Even for loadings higher than a theoretical V 2 O 5 monolayer, only a small fraction (≈10%) of the TiO 2 surface is covered by "towers" (i.e., vertical-growth) of polycrystalline V 2 O 5 . 33 In addition, their surfaces contain few free surface Ti atoms, which likely exist in real systems leading to possible interactions with the water vapor present in the flue gas.…”
Section: ■ Introductionmentioning
confidence: 96%
“…This section describes each element in turn. Niksa and Fujiwara (2005) introduced the first reaction mechanism for simultaneous NO reduction and Hg 0 oxidation along SCRs in terms of lumped catalyst reactivities that resolved film transport of reactants onto the external catalyst channel wall from an overall chemical reactivity. The key features were a competition between NH 3 and HCl for surface sites, and an Hg°oxidation reaction on chlorinated sites.…”
Section: Scr Unit Simulationsmentioning
confidence: 99%